2016
DOI: 10.1111/scs.12370
|View full text |Cite
|
Sign up to set email alerts
|

The role of ICT in nursing practice: an integrative literature review of the Swedish context

Abstract: Although ICT cannot replace physical presence, it can be considered a complementary service that gives rise to improved patient care. However, nonverbal communication cues may be missed when ICT is used as mediating tool and ICT can be limiting because it is not always designed to meet nurse and patient needs. The meaning of an encounter appears to change when ICT is used in nursing practice, not only for patient relationships but also for interpersonal communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 58 publications
(188 reference statements)
2
54
1
2
Order By: Relevance
“…Done properly, this would help the DNs to see eHealth as a help rather than a hindrance. This finding is consistent with another Swedish review which also shows that the digitalisation of health care can be perceived as both supporting and inhibiting and arouses ambivalence among caregivers. Related to this, it is important that we come to a better understanding of healthcare processes so that new systems can be designed accordingly.…”
Section: Discussionsupporting
confidence: 91%
“…Done properly, this would help the DNs to see eHealth as a help rather than a hindrance. This finding is consistent with another Swedish review which also shows that the digitalisation of health care can be perceived as both supporting and inhibiting and arouses ambivalence among caregivers. Related to this, it is important that we come to a better understanding of healthcare processes so that new systems can be designed accordingly.…”
Section: Discussionsupporting
confidence: 91%
“…This in contrast to a study by Gautun et al, [37] where only a few informal caregivers indicated worsened health resulting from caregiving duties. Fagerstrom et al [38] argued that the use of ICT in health service settings can allow patients and their informal caregivers to communicate with their care manger when face-to face contact is not possible. However, they noted that the ICT cannot replace personal attendance.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…When health IT is operating as a tool that aids cooperation between healthcare organisations, staff need to feel that they can trust the tools and the information they comprise (Lluch, 2011). In many instances, new ways of working have not been harmonised with organisational cultures, the values of the work context and routines (Fagerstrom, Tuvesson, Axelsson, & Nilsson, 2016). According to Fagerstrom et al (2016), nursing practice is influenced by the role of digitised tools, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, new ways of working have not been harmonised with organisational cultures, the values of the work context and routines (Fagerstrom, Tuvesson, Axelsson, & Nilsson, 2016). According to Fagerstrom et al (2016), nursing practice is influenced by the role of digitised tools, i.e. information and communication technology in patient care, working conditions, and nurses' professional identity and continuous professional development.…”
Section: Introductionmentioning
confidence: 99%